Ill. bij gedicht "De natuurlijke historie van de Christelijke regeeringsmeerderheid" door L.M. Hermans. . V.l.n.r.:G. Kruys, J.J.I. Harte van Tecklenburg, J.W. Bergansius, ?, Abraham Kuyper, J.A. Loeff, R. Melvil baron van Lynden, J.C. de Marez-Oyens - Hahn, Albert,
Ill. bij gedicht "De natuurlijke historie van de Christelijke regeeringsmeerderheid" door L.M. Hermans. V.l.n.r.:G. Kruys, J.J.I. Harte van Tecklenburg, J.W. Bergansius, ?, Abraham Kuyper, J.A. Loeff, R. Melvil baron van Lynden, J.C. de Marez-Oyens.